Ice cold - Gerritsen, Tess (Gerritsen, Tess. Rizzoli & Isles novel., 2010)
Boston homicide detective Jane Rizzoli receives the grim news that Maura's charred body has been found in a mountain ravine. Shocked and grieving, Jane is determined to learn what happened to her friend. The investigation plunges Jane into the twisted history of Kingdom Come, Wyoming, where a gruesome discovery lies buried beneath the snow.